POSITIVE INFLUENCE OF EXERCISE AND PHYSICAL ACTIVITY ON THE HUMAN BODY - Czarnecki, D.; Skalski, D. W.; Kowalski, D.; Graczyk, M.; Kindzer, B.; Gaynulina, I. (Rehabilitation and Recreation, 2022)
The most important factors that have a significant impact on health and life expectancy are physical activity. Physical activity is a very important element in human life. As planned, extra effort, it significantly shapes both the personality and health potential. As a result of media support, the physical development of an individual is particularly endorsed in modern society. Recommendations concerning healthy eating, training and the principles of a healthy lifestyle in general, reaching from all over the world, play an important role in building health awareness. The benefits of physical activity are obvious. Systematic physical activity is a very strong biological stimulator and is one of the main determinants of human physical and mental health. In theory, physical activity is dedicated to all people who are capable of doing it. Broadly understood physical activity includes recreational physical activity (including most amateur sports and dance), professional sports, physical activity at home and in the vicinity, and physical activity related to transport / mobility. Factors influencing the degree of physical activity are environmental factors, such as topography and buildings, the existing sports infrastructure, and economic and social factors. An important factor is also the way of getting around, which has also undergone significant changes in recent years, in particular using the car to a greater extent than in the past. In such conditions, the role of physical activity increases in ensuring a high level of health, increasing life expectancy, and maintaining human capacity for work. Thanks to physical activity, productivity and quality of life are ensured. This is a component of the success of every person, regardless of the field of work. Giving up physical activity can lead to diabetes, obesity, heart and circulatory system diseases, as well as changes in the joints and spine.